Quantitative proteomics approach reveals novel biomarkers and pathological mechanism of keloid. Issue 4 (26th April 2022) - Liu, Jian; Yang, Chunhua; Zhang, Huayu; Hu, Wei; Bergquist, Jonas; Wang, Helen; Deng, Tingzhi; Yang, Xueling; Zhang, Chao; Zhu, Yanping; Chi, Xiaodong; Mi, Jia; et al.
Abstract: Background: Keloid is a pathological skin scar formation with complex and unclear molecular pathology mechanism. Novel biomarkers and associated mechanisms are needed to improve current therapies. Objectives: To identify novel biomarkers and underlying pathological mechanisms of keloids. Methods: Six pairs of keloid scar tissues and corresponding normal skin tissues were quantitatively analyzed by a high‐resolution label‐free mass spectrometry‐based proteomics approach. Differential protein expression data was further analyzed by a comprehensive bioinformatics approach to identify novel biomarkers and mechanistic pathways for keloid formation. Candidate biomarkers were validated experimentally. Results: In total, 1359 proteins were identified by proteomic analysis. Of these, 206 proteins exhibited a significant difference in expression between keloid scar and normal skin tissues. RCN3 and CALU were significantly upregulated in keloids. RCN1 and PDGFRL were uniquely expressed in keloids. Pathway analysis suggested that the XBP1‐mediated unfolded protein response (UPR) pathway was involved in keloid formation. Moreover, a PDGFRL centric gene coexpression network was constructed to illustrate its function in skin. Conclusions and Clinical Relevance: Our study proposed four novel biomarkers and highlighted the role of XBP1‐mediated UPR pathway in the pathology of keloids. It provided novel biological insights that contribute to develop novel therapeutic strategies for keloids.